2002
DOI: 10.1021/es011311s
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Mass Balance of 2,3,7,8-TeCDD in Aqueous Solution under UV Light Shows Formation of Chlorinated Dihydroxybiphenyls, Phenoxyphenols, and Dechlorination Products

Abstract: Polychlorinated dibenzo-p-dioxins (PCDDs) are a class of halogenated diaryl compounds that are environmentally important because of their high toxicity and bioaccumulatory properties. There is an incomplete understanding of their photochemistry because the majority of photoproducts, as indicated by incomplete mass balances, have not been identified. We studied the photochemical transformation of 2,3,7,8-tetrachlorodibenzo-p-dioxin (2,3,7,8-TeCDD) in aqueous solution using 302 nm light. Our results allow for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…Several methods have been considered in the development of an efficient and economically feasible approach for destroying PCDD/Fs, including catalytic destruction [9,10], photolysis [11][12][13][14][15][16], photocatalysis [17], radiolysis [18], ozonolysis [19], and biodegradation [20,21]. Dechlorination is generally reported as the predominant reaction, and dechlorinated products have been identified in different solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been considered in the development of an efficient and economically feasible approach for destroying PCDD/Fs, including catalytic destruction [9,10], photolysis [11][12][13][14][15][16], photocatalysis [17], radiolysis [18], ozonolysis [19], and biodegradation [20,21]. Dechlorination is generally reported as the predominant reaction, and dechlorinated products have been identified in different solvents.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the differences between the photodegradation mechanisms of PCDD/Fs. Rayne et al [16] examined the photochemical transformation of 2,3,7,8-TCDD in aqueous solution, using 302 nm light and indicated that the major primary product of 2,3,7,8-TCDD is 2,2 -dihydroxy-4,4 ,5,5 -tetrachlorobiphenyl (4,4 ,5,5 -TeCDHBP). The findings reveal that the photochemical conversion of PCDDs to chlorinated dihydroxybiphenyls may be the most important factor in determining the environmental fate of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of other dlPCBs slows down the decrease in TEq and may even increase it (Miao et al 1999). PCBs produce OH-derivatives (Tysklind et al 1993, Rayne et al 2002.…”
Section: Photochemical Transformation and Decaymentioning
confidence: 99%
“…In research efforts during the 1960s through 1980s, the groups of Hewgill [1][2][3][4][5][6][7] and Becker [8,9] employed oxidative approaches to generate-and in some cases isolate-these elusive compounds. More recently, during the 1990s and 2000s, it was shown that 2,2 0 -diphenoquinones may be photochemically generated from a range of dibenzo [1,4]dioxins (including the parent system) having electron withdrawing and donating groups [10][11][12][13], as well as via traditional thermal oxidative methods with 3,3 0 ,5,5 0 -tetraaryl substituents (e.g., phenyl and 4-methoxyphenyl) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expected different spectral properties of the cis/trans isomers, and their potential thermal/excited state interconversions, offer possible utility as molecular switch motifs. The ability to generate 2,2 0 -diphenoquinones photochemically from the well-known chlorinated dibenzo [1,4]dioxin environmental contaminants, as well as via thermal oxidation of polychlorinated biphenyl (PCB) metabolites (i.e., chlorinated-2,2 0 -dihydroxybiphenyls), also warrants further mechanistic investigation regarding their role in the toxicological effects of the parent compounds [12,15]. Consequently, in this study we employ various levels of theoretical methods to examine substituent and solvent effects on the cis/trans isomerization equilibrium of 2,2 0 -diphenoquinones, as well as the thermodynamics of their intramolecular rearrangements.…”
Section: Introductionmentioning
confidence: 99%